PHILOSOPHICAL KNOWLEDGE IN THE HISTORICAL RESEARCH - Nechuhrin, Aleksandr; Syniakov, Sergii; Skyba Іvan (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2023)
The mechanisms of interrelation between ideological values and methodological means of historical perception are revealed in the article. The role of philosophy as a theoretical center of the ideology is underlined in the article. The participation of philosophical ideas in the formation of historical conceptions and categorical mechanisms of historical science, in the evolution of historical concepts, in the development of the methods of the perception of the past and the subject field of the research is discussed in the article. The authors underline the specific features of historical perception, the importance of microideas which show the unique nature of social phenomena of the past for it. The change in the system of concepts of historical science in connection with the change of philosophical conceptions as well as historical approaches (social history, "Annals" school, new social history) is shown in the article.